2015
DOI: 10.1007/s10157-015-1143-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of physical and psychosocial problems associated with diabetic nephropathy using the International Classification of Functioning, Disability and Health Core Set for Diabetes Mellitus

Abstract: The results of this study using the ICF-CS for DM identified the areas for improvement among physical and psychosocial problems in DMN patients with and without HD in contrast to diabetes patients without nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…This suggest that complications increase in DM patients with age. Tsutsui et al also found the same observations in their study [8]. The subjects with DPN showed more sensory disturbances and urinary dysfunction.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…This suggest that complications increase in DM patients with age. Tsutsui et al also found the same observations in their study [8]. The subjects with DPN showed more sensory disturbances and urinary dysfunction.…”
Section: Discussionsupporting
confidence: 70%
“…DPN patients were significantly more likely to experience problems associated with 10 categories out of 18 categories under activity and participation. Tsutsui et al observed almost similar results in his study on DM patients with nephropathy [8]. Patients with diabetes mellitus with and without neuropathy reported that they received support from their family and friends while they suffered from DM or DPN and that became their facilitator.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…For this reason, the ICF research branch proposed and introduced the ICF Core Set for stroke in 2004 to facilitate the use of the ICF in clinical practice (4,5). The ICF Core Set contents (which were developed for particular health conditions and settings) have been validated for several health conditions (6)(7)(8) including stroke (9)(10)(11)(12)(13)(14). In addition, the inter-rater and intra-rater reliability of ICF categories with additional scoring guidelines, as well as the usefulness of ICF categories as outcome measures, have also been determined (15).…”
Section: Introductionmentioning
confidence: 99%